Impacto de políticas públicas em comunidade quilombola: Senhor do Bonfim-PB, Brasil - Yogi, Euriko dos Santos (2014)
This research discussed the impacts of public policies for family farming on traditional knowledge and agricultural practices in maroon community Senhor do Bonfim-PB. Part of the hypothesis that these policies by prioritizing economic side, insert the community elements of the modernized agriculture, something inconsistent with the text of the law to encourage family farming which had the objective of social, environmental and economic sustainability. We used qualitative research using semi-structured interviews, participant observation and participatory methodologies. We found that some public policies influencing the farmers' productive way, these actions end up inserting elements in the modernization of agriculture and influence the mode of production.